PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUASAN KONSUMEN PADA PRODUK SURYA MAKMUR BATAM CENTRE - Ganda, Ganda Wijaya; Syaifullah (LPPM Universitas Putera Batam, 2022)
The objectives of this research are to: (1) assess the impact of product quality on customer satisfaction; and (2) determine the impact of product quality on consumer satisfaction.(2) Assess the impact of brand image on customer satisfaction.(3) assess the impact of product quality and brand image on customer satisfaction. This study is based on a connection.The Slovin formula was used to calculate the sample size, yielding a sample size of 178 persons.In this study, the hypothesis test is a multiple linear regression test.Based on the findings of the data analysis, a significance value of 0.0000.05 was achieved, indicating that product quality has a substantial impact on customer satisfaction.The significance value of the brand image variable was 0.002 0.05, indicating that brand image had a substantial influence on customer satisfaction with Surya Makmur Batam Center goods, according to the findings of data analysis.With a 0.0000.05 significant value, it can be inferred that product quality and brand image factors have an impact on customer satisfaction with Surya Makmur Batam Center items.Keywords: Brand Image, Consumer Satisfaction, Product Quality